2012
DOI: 10.1017/s0025315412000677
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structuring of submerged aquatic vegetation in an estuarine habitat of the Gulf of Mexico

Abstract: Seasonal changes in spatial structure of biomass of submerged aquatic vegetation (SAV) and environmental variables were evaluated in Celestun Lagoon, an estuarine habitat in Mexico. Geostatistical techniques were used to evaluate spatial autocorrelation and to predict the spatial distribution by kriging. The relative contribution of 11 environmental variables in explaining the spatial structure of biomass of SAV was evaluated by canonical correspondence analysis. Spatial partitioning between species of SAV was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 35 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…In order to understand the spatial distribution of copper throughout the Guarapiranga ELU, a kriging interpolation method was implemented using Geovisual v. 5.0 software, following the procedure of Yamamoto and Landim (2015). This technique has been used in other similar studies (Smal, 2015;Batista, 2011;Alcantara, 2008;Burgos-León et al, 2012), and it has been shown to be an excellent tool for spatial analysis (Cressie, 1993;Camargo et al, 1999Camargo et al, , 2001Machado et al, 2004).…”
Section: Copper Spatial Interpolation and Spatial Analysismentioning
confidence: 99%
“…In order to understand the spatial distribution of copper throughout the Guarapiranga ELU, a kriging interpolation method was implemented using Geovisual v. 5.0 software, following the procedure of Yamamoto and Landim (2015). This technique has been used in other similar studies (Smal, 2015;Batista, 2011;Alcantara, 2008;Burgos-León et al, 2012), and it has been shown to be an excellent tool for spatial analysis (Cressie, 1993;Camargo et al, 1999Camargo et al, , 2001Machado et al, 2004).…”
Section: Copper Spatial Interpolation and Spatial Analysismentioning
confidence: 99%